2017
DOI: 10.3390/ijms18061130
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Inhibits Androgen Receptor Splice Variant-7 (AR-V7)-Induced Nuclear Factor-Kappa B (NF-κB) Activation and NF-κB Activator-Induced AR-V7 Expression in Prostate Cancer Cells: Potential Implications for the Use of Melatonin in Castration-Resistant Prostate Cancer (CRPC) Therapy

Abstract: A major current challenge in the treatment of advanced prostate cancer, which can be initially controlled by medical or surgical castration, is the development of effective, safe, and affordable therapies against progression of the disease to the stage of castration resistance. Here, we showed that in LNCaP and 22Rv1 prostate cancer cells transiently overexpressing androgen receptor splice variant-7 (AR-V7), nuclear factor-kappa B (NF-κB) was activated and could result in up-regulated interleukin (IL)-6 gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 37 publications
(75 reference statements)
1
34
0
Order By: Relevance
“…In the normal cells, the reversed equilibrium is expected since melatonin protects normal cell from apoptosis and other cellular injuries (65)(66)(67)(68)(69). Many studies have observed that melatonin treatment has beneficial effects on normal cells but induces apoptosis in tumor cells (70)(71)(72)(73)(74). Under melatonin treatment, large quantity of cytochrome C is released from the mitochondria into cytosol to induce apoptosis in tumor cells (75)(76)(77) while and the cytochrome C release is inhibited in the normal cells by melatonin (75,(78)(79)(80).…”
Section: Melatonin Metabolism In Mitochondriamentioning
confidence: 99%
“…In the normal cells, the reversed equilibrium is expected since melatonin protects normal cell from apoptosis and other cellular injuries (65)(66)(67)(68)(69). Many studies have observed that melatonin treatment has beneficial effects on normal cells but induces apoptosis in tumor cells (70)(71)(72)(73)(74). Under melatonin treatment, large quantity of cytochrome C is released from the mitochondria into cytosol to induce apoptosis in tumor cells (75)(76)(77) while and the cytochrome C release is inhibited in the normal cells by melatonin (75,(78)(79)(80).…”
Section: Melatonin Metabolism In Mitochondriamentioning
confidence: 99%
“…Conversely, in other systems such as Cos7 fibroblasts, HEK293 and MCF7 cells, activation of Gαq and Gαs proteins coupled to MT1 receptors leads to an increase of cAMP formation. Increased intracellular cAMP in turn activates PKA and PKC, which causes the inhibition of NF-ΚB (Nuclear Factor Kappa-light-chain-enhancer of activated B cells) with consequent derepression of the oncosuppressor p27 kip1 and attenuation of the androgen response in prostate cells [ 53 , 54 , 55 , 65 , 66 , 67 ], activation of JNK in Cos7 cells [ 68 ], and phosphorylation of ERK1/2 in HEK 293 cells [ 69 ].…”
Section: Melatonin Membrane Receptorsmentioning
confidence: 99%
“…Moreover, melatonin has been shown to inhibit the expression of stemness-related genes, [ 105 , 128 , 129 ] to inhibit stemness-related pathways [ 105 , 106 ] to improve the response to several anticancer therapies [ 102 , 103 , 130 , 131 , 132 , 133 , 134 ], and to inhibit angiogenesis [ 127 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ]. Finally, in Androgen Receptor (AR) and Estrogen Receptor (ER) positive cells, melatonin inhibits the AR [ 54 , 65 , 147 , 148 , 149 ] and ER response [ 128 , 150 , 151 , 152 , 153 ] through different mechanisms either mediated by MT1 or independent of MT1 receptor binding.…”
Section: Oncoprotective Role Of Melatonin: In Vitro Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…NF-κB pathway regulates the expression of a large number of genes, which are crucial for the regulation of apoptosis, virus replication, tumorigenesis, inflammation and various autoimmune diseases [11][12][13][14]. Bacterial infection or LPS simulation activates NF-κB pathway which promotes the production of inflammatory cytokines [15].…”
Section: Introductionmentioning
confidence: 99%